Integrated 3D printing and case-based learning in orthopedic residency education for geriatric hip fracture management - Wang, Honglin; Yang, Tao; Hua, Wei; Zhang, Wentao; Lu, Lin (Frontiers in Surgery, 2025)
ObjectiveGeriatric hip fractures, clinically designated as “the last fracture in life” due to significant disability and mortality, pose critical educational barriers for orthopedic residents in mastering complex hip anatomy and surgical decision-making competencies. This study evaluates the implementation value of integrating digital 3D-printing technology with CBL pedagogy in standardized residency training for geriatric hip fracture management.MethodsFifty-six orthopedic residents undergoing standardized training at Renmin Hospital of Wuhan University were enrolled and randomly assigned to either the control group (CBL, n = 28) or the experimental group (CBL-3DP, n = 28). Both groups received training in surgical planning for geriatric hip fractures. The CBL group underwent traditional CBL teaching, while the CBL-3DP group combined CBL with 3D-printed fracture models. Post-training assessments evaluated theoretical knowledge, practical skills, satisfaction, and engagement with the teaching methodology.ResultsFollowing the instructional intervention, the CBL-3DP group demonstrated significantly superior performance compared to the conventional CBL group in both theoretical and practical assessments. Theoretically, the CBL-3DP cohort achieved higher scores in regional anatomy comprehension, fracture classification accuracy, and mastery of treatment principles (p < 0.05). Practically, this group exhibited enhanced competencies in geriatric hip fracture management domains including patient consultation, physical examination, diagnostic precision, basic emergency management, and preoperative surgical planning (p < 0.05). Questionnaire analyses further indicated that the 3D + CBL approach yielded significantly better outcomes than traditional CBL in: depth of understanding of geriatric hip fractures, learning enthusiasm, diagnostic capabilities, surgical planning proficiency, confidence in managing clinical cases, and satisfaction with the instructional methodology.ConclusionThe integration of 3D printing with CBL methodology enhances training effectiveness and learner satisfaction in geriatric hip fracture education, supporting its adoption in standardized orthopedic residency programs.